Simulation of a calcium looping CO2 capture process for pressurized fluidized bed combustion - Duhoux, Benoit; Symonds, Robert T.; Hughes, Robin; Mehrani, Poupak; Anthony, Edward J.; Macchi, Arturo (Wiley, 2019)
The Canadian regulations on carbon dioxide emissions from power plants aim to lower the emissions from coal‐fired units down to those of natural gas combined cycle (NGCC) units. Since coal is significantly more carbon intensive than natural gas, coal‐fired plants must operate at higher net efficiencies and implement carbon capture to meet the new regulations. Calcium looping (CaL) is a promising post‐combustion carbon capture (PCC) technology that, unlike other capture processes, generates additional power. By capturing carbon dioxide at elevated temperatures, the energy penalty that carbon capture technologies inherently impose on power plant efficiencies is significantly reduced. In this work, the CO2 capture performance of a calcium‐based sorbent is determined via thermogravimetric analysis under relatively high carbonation and low calcination temperatures. The results are used in an aspenONE™ simulation of a CaL process applied to a pressurized fluidized bed combustion (PFBC) system at thermodynamic equilibrium. The combustion of both natural gas and coal are considered for sorbent calcination in the CaL process. A sensitivity analysis on several process parameters, including sorbent feed rate and carbonator operating pressure, is undertaken. The energy penalty associated with the capture process ranges from 6.8 –11.8 percentage points depending on fuel selection and operating conditions. The use of natural gas results in lower energy penalties and solids circulation rates, while operating the carbonator at 202 kPa(a) results in the lowest penalties and drops the solids circulations rates to below 1000 kg/s.
Keywords: Carbon capture; calcium looping; pressurized FBC; process simulation